Elitist democracy, university and counterwrites - Castillo, Alejandra (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
The purpose of this paper is to describe the university in Chile from the frame of the elitist and corporate democracy. In order to achieve this purpose, firstly we will define the elitist democracy. Secondly, we make explicit the relation between University and the idea of excellence, keyword in elitist and corporate democracys. And thirdly, we present the independent editorials as a university countwrite machine